Manajemen Pendidikan Karakter PAUD Terpadu ‘Aisyiyah Nur’aini Ngampilan Yogyakarta - Yuliani, Bustanul (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2016)
Children is a state asset which will be the successor to the nation in the future, so that in the formation of character is the most important thing at early childhood education. From that problem, the management of character education in early childhood education (ECD) at PAUD Terpadu 'Aisyiyah Nur'aini by the planning, actuating, monitoring and coaching. Character values ​​embedded in early childhood are 15 character values. Factors that influence the character education management in early childhood can be seen with the SWOT analysis and found to external factors (opportunities and threats) and internal (strengths and weaknesses). Furthermore, the impact of early childhood education management in the characters that can be seen in the future, but there is some value character that has an effect on positive behavior change and polite language and thought patterns are changing for the better, so that the child is directed when in school and at home.